To solve this equation, we need to use the distributive property and combine like terms.
First, let's simplify the left side of the equation:
x(8 + 2) + 3 = (x * 8) + (x * 2) + 3 = 8x + 2x + 3 = 10x + 3
Now, let's simplify the right side of the equation:
2(5 + x) + 5(x + 1) − 6 = (2 * 5) + (2 * x) + (5 * x) + (5 * 1) - 6 = 10 + 2x + 5x + 5 - 6 = 7x + 9
Now, we can set the left side equal to the right side and solve for x:
10x + 3 = 7x + 9
Subtract 7x from both sides:
10x - 7x + 3 = 7x - 7x + 9
3x + 3 = 9
Subtract 3 from both sides:
3x + 3 - 3 = 9 - 3
3x = 6
Divide both sides by 3:
3x/3 = 6/3
x = 2
Therefore, the answer is x = 2.
The correct response is C) 22.
x(8 + 2) + 3 = 2(5 + x) + 5(x + 1) − 6
Responses
A −4−4
B −2−2
C 22
D 4
1 answer